Registry of implants for the reconstruction of pelvic floor in males and females: a feasibility case series - Barski, Dimitri; Pelzer, Alexandre E. (International journal of surgery, 2017)
Introduction: Most aspects of implant-assisted reconstruction of pelvic floor in males and females are under debate and the research is not standardized. Registries are supposed to shed light to the indications, surgical techniques and material properties and to establish a standardized evaluation. Methods: A working group was formed to create an online platform for registration and outcome measurement of implant-assisted operations for pelvic organ prolapse (POP) and female and male stress urinary incontinence (SUI). 20 patients with modified mesh materials were evaluated over 23 months follow up in the registry to prove the feasibility of the registry. For validation a previously published modified “satisfaction, anatomy, continence, safety - S.(A.)C.S score” was used. Results: A consensus was met on definitions and classifications of patient variables, surgical procedures and implants, as well as outcome parameters (efficacy, continence, satisfaction, complications). Different subgroup modules were formed in accordance with treated condition. The maximum score of cure was reached by 25-100% of patients depending on the indication. Conclusion: A prospective registry in accordance with IDEAL-D framework is justified for the evaluation and regulation of implants for pelvic floor reconstruction.
Available online 15 April 2017
Gesehen am 25.10.2018